Analyse des exercices écrits au collège : Quelle place à la dimension réflexive ? - BENLEHLOUH, Khaoula Amina (Journal of Human Sciences, 2022)
In the current era the backbone of activities designed for teaching / learning French as a foreign language is reflection. Getting the learner to adopt a reflective posture and to assume his responsibility as a partner in the negotiation and the construction of knowledge is an objective that the reader can come across in the current teaching material introductions. This progressive and conscious construction of knowledge is supposed to lead to more efficient learning, especially in writing. Here, the role of the exercise, which often focuses on a fragmentary part of the language, appears as a structuring agent, even a guarantee of the transfer of knowledge to target situations. What about the Algerian context? This present contribution intends to examine the role assigned to the written exercise, more specifically the one dealing with language points, in the light of these theoretical precepts.